Using Preliminary Risk Analysis (PRA) to Ensure Safety in the Preparation Process for Parenteral Nutrition Bags in Hospital Pharmacy - Le Pêcheur Véronique; Spiesser-Robelet Laurence; Vrignaud Sandy (De Gruyter, 2016)
Objectives: The aim of this paper is to use the Preliminary Risk Analysis (PRA) method to assess the criticality of the different stages in the process of preparing parenteral nutrition bags for use in neonatal resuscitation and, if necessary, improve the handling of the process itself.